High-activity humic acid ecological compound fertilizer

By using highly active humic acid and multi-layer coating technology in fertilizers, an efficient slow-release compound fertilizer was prepared, which solved the problems of short delayed release time and unstable controlled release effect of existing fertilizers, achieved long-term nutrient release and efficient utilization, and reduced environmental pollution.

CN119859075APending Publication Date: 2025-04-22SHANGHAI WINTONG ECOLOGICAL ENGINEERING CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411799379.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-09
Publication Date
2025-04-22

AI Technical Summary

Technical Problem

In actual applications, existing sustained and controlled release fertilizers have problems such as short delayed release time, unstable controlled release effect, unfriendly coating materials to the environment, and difficult to adjust the nutrient release rate.

Method used

Highly active humic acid is used as the main component, and through multi-layer coating technology, the inner layer is a blend of polylactic acid and polycaprolactone, the middle layer is a composite of nanosilicon dioxide and nanoalumina, and the outer layer is a hydrogel of chitosan and polyacrylic acid. Compound fertilizer with long-term sustained release effect is prepared by spray drying and fluidized bed coating technology.

Benefits of technology

Long-term sustained release of nutrients is achieved, and the continuous release time can reach 3 to 9 months, meeting the nutritional needs of crops in different growth cycles, reducing the frequency of fertilization, improving fertilizer utilization, and significantly reducing the risk of environmental pollution.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119859075A_ABST
    Figure CN119859075A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of agricultural planting, and discloses a high-activity humic acid ecological compound fertilizer which comprises the following components in percentage by mass: 5-40% of high-activity humic acid; 10% to 35% of nitrogen; 5%-20% of phosphorus; 5%-20% of potassium; 0.1%-5% of chelated trace elements including iron, zinc and copper; 2%-20% of an inner layer coating material; 0.5%-10% of a middle layer coating material; 0.5%-5% of an outer layer coating material; the inner-layer coating material is formed by blending polylactic acid and polycaprolactone, and nano silicon dioxide particles are added in the blending process. Through a multi-layer coating technology, the compound fertilizer can realize long-acting nutrient slow release, the nutrient release period is prolonged, the nutrient release of the compound fertilizer can last for 3-9 months, the nutritional requirements of crops in different growth periods are effectively met, the fertilization frequency is reduced, and the utilization rate of the fertilizer is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of agricultural planting, in particular to a high-activity humic acid ecological compound fertilizer. Background Art

[0002] With the development of global agricultural production, the requirements for crop yield and quality are constantly increasing, and the role of fertilizers in agricultural production is becoming more and more important. Traditional chemical fertilizers, especially conventional compound fertilizers, can provide the basic nutrients (such as nitrogen, phosphorus, and potassium) required for crop growth, but there are many limitations. First, traditional compound fertilizers are easy to dissolve quickly in the soil, resulting in a large amount of nutrients released in a short period of time. This not only fails to meet the nutritional needs of the entire growth cycle of crops, resulting in a short fertilizer effect period, but also easily causes nutrient loss and environmental pollution problems, such as groundwater pollution and eutrophication of water bodies caused by excessive application of nitrogen fertilizers. In addition, the existence form of trace elements in traditional compound fertilizers is usually unstable and easily affected by soil conditions and loses activity, thereby reducing the absorption efficiency of these elements by crops, resulting in unsatisfactory fertilization effects.

[0003] In order to solve the above problems, slow-release fertilizers and controlled-release fertilizers came into being. Slow-release fertilizers delay the release rate of nutrients by changing the physical structure or chemical properties of fertilizers, while controlled-release fertilizers form one or more coating layers on the surface of fertilizer particles through coating technology to control the nutrient release rate. However, existing slow-release and controlled-release fertilizers still have shortcomings in practical applications, such as short slow-release time, unstable controlled-release effect, environmentally unfriendly coating materials, and difficulty in adjusting the nutrient release rate according to the needs of different crops. In addition, the coating materials used in some slow-release fertilizers are difficult to degrade in the soil, and long-term application may cause changes in the physical structure of the soil and even affect the soil ecosystem.

[0004] To this end, those skilled in the art provide a high-activity humic acid ecological compound fertilizer to solve the problems raised in the above background technology. Summary of the invention

[0005] In view of the shortcomings of the prior art, the present invention provides a highly active humic acid ecological compound fertilizer, which solves the problems in the prior art of short sustained-release time, unstable controlled-release effect, environmentally unfriendly coating materials, and difficulty in adjusting the nutrient release rate according to the needs of different crops.

[0006] To achieve the above purpose, the present invention is implemented by the following technical scheme: a highly active humic acid ecological compound fertilizer, comprising the following components in percentage by mass:

[0007] 5% to 40% highly active humic acid;

[0008] 10% to 35% nitrogen;

[0009] 5% to 20% phosphorus;

[0010] 5% to 20% potassium;

[0011] 0.1% to 5% chelated trace elements;

[0012] 2% to 20% inner coating material;

[0013] 0.5% to 10% of middle layer coating material;

[0014] 0.5% to 5% outer coating material.

[0015] Preferably, the inner layer coating material is a mixture of polylactic acid and polycaprolactone in a ratio of 50:50 to 90:10, and 5% to 15% by mass of nano-silicon dioxide particles are added to the mixture based on the total inner layer coating material.

[0016] Preferably, the middle layer coating material is a composite coating of nano-silicon dioxide and nano-aluminum oxide prepared by a sol-gel method, and the thickness thereof is 5 μm to 30 μm.

[0017] Preferably, the outer coating material is a hydrogel prepared from a copolymer of chitosan and polyacrylic acid, and the mass ratio of chitosan to polyacrylic acid is 1:1 to 1:3.

[0018] Preferably, the thickness of the inner coating material is 10 μm to 50 μm, the thickness of the middle coating material is 5 μm to 30 μm, and the thickness of the outer coating material is 5 μm to 20 μm.

[0019] Preferably, the chelated trace elements include one or more of iron, zinc and copper.

[0020] A method for preparing a high-activity humic acid ecological compound fertilizer, comprising the following steps:

[0021] (1) Extraction of highly active humic acid;

[0022] (2) Modification of highly active humic acid and chelation of trace elements;

[0023] (3) using a high-speed mixer to mix the modified high-activity humic acid with nitrogen, phosphorus and potassium, and then using spray drying technology to prepare particles;

[0024] (4) Fluidized bed coating technology is used to control the thickness of the coating layer of the core particles, wherein the inner layer is a blend of polylactic acid and polycaprolactone, the middle layer is a composite material of nano-silicon dioxide and nano-alumina, and the outer layer is a hydrogel prepared from a copolymer of chitosan and polyacrylic acid;

[0025] (5) The coated particles are dried using vacuum drying technology and then bagged for storage.

[0026] Preferably, the highly active humic acid extraction step in step (1) comprises:

[0027] A. After the weathered coal or lignite raw material is crushed, humic acid is extracted using 5% to 15% sodium hydroxide at 60°C to 90°C, and after filtering, the pH is adjusted to 1.0 to 3.0 to precipitate humic acid, which is then dried and crushed;

[0028] B. The extracted humic acid is reacted with ethylenediamine or sodium bisulfite at 40°C to 70°C for 1h to 5h to form modified humic acid, which is then mixed with trace elements of iron, zinc and copper, the pH is adjusted to 4.0 to 7.0, and stirred for 1h to 3h to obtain highly active humic acid.

[0029] Preferably, the vacuum drying conditions in step (5) are: temperature of 40°C to 60°C, vacuum degree of 0.05MPa to 0.1MPa, and drying time of 2h to 6h, to ensure that the moisture content in the particles is reduced to below 1%.

[0030] Preferably, the inlet temperature of the spray drying in step (3) is 120°C to 160°C, and the outlet temperature is 70°C to 90°C.

[0031] The present invention provides a highly active humic acid ecological compound fertilizer, which has the following beneficial effects:

[0032] 1. The present invention uses multi-layer coating technology to enable the compound fertilizer to achieve long-term nutrient slow release. The inner coating material is a blend of polylactic acid and polycaprolactone, combined with the reinforcing effect of nano-silicon dioxide particles, which ensures that the fertilizer can stably release the main nutrients in the early stage after application. The middle and outer coating materials further extend the nutrient release cycle, so that the nutrient release of the compound fertilizer can last for 3 to 9 months, effectively meeting the nutritional needs of crops in different growth cycles, reducing the frequency of fertilization, and improving fertilizer utilization.

[0033] 2. After being modified by humic acid, the chelated trace elements of the present invention form a stable chelated state with trace elements such as iron, zinc, and copper, which significantly improves the stability of these trace elements in the soil and the plant absorption rate.

[0034] 3. The present invention significantly reduces the loss of nutrients in a short period of time through coating and slow-release technology, avoiding the soil and water pollution caused by excessive fertilization. In addition, the coating materials in the compound fertilizer, such as polylactic acid and polycaprolactone, are degradable materials, which reduces the environmental burden and helps promote the sustainable development of agriculture.

[0035] 4. The present invention can adapt to different soil conditions and climatic environments by adjusting the thickness of the coating layer and the material ratio. It can maintain a stable fertilizer effect regardless of whether it is in a high temperature and high humidity or a low temperature and drought environment, and is suitable for promotion and use in various agricultural production environments. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] Figure 1 It is a schematic diagram of the preparation steps of the present invention. DETAILED DESCRIPTION

[0037] The technical solution of the present invention will be described clearly and completely below in conjunction with the accompanying drawings of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0038] Embodiment 1:

[0039] Please see attached Figure 1 The embodiment of the present invention provides a high-activity humic acid ecological compound fertilizer, comprising the following components in percentage by mass:

[0040] 5% to 40% of highly active humic acid; 10% to 35% of nitrogen; 5% to 20% of phosphorus; 5% to 20% of potassium; 0.1% to 5% of chelated trace elements, including iron, zinc, and copper; 2% to 20% of inner coating material; the inner coating material is a mixture of polylactic acid and polycaprolactone in a ratio of 50:50 to 90:10, and 5% to 15% by mass of nano-silicon dioxide particles are added to the mixture. 0.5% to 10% of middle coating material; the middle coating material is a nano-silicon dioxide and nano-alumina composite coating prepared by a sol-gel method, and its thickness is 5μm to 30μm. 0.5% to 5% of outer coating material; the outer coating material is a hydrogel prepared from a copolymer of chitosan and polyacrylic acid, and the mass ratio of chitosan to polyacrylic acid is 1:1 to 1:3.

[0041] The thickness of the inner coating material is 10 μm to 50 μm, the thickness of the middle coating material is 5 μm to 30 μm, and the thickness of the outer coating material is 5 μm to 20 μm.

[0042] According to the above formula, a method for preparing a highly active humic acid ecological compound fertilizer is provided, comprising the following steps:

[0043] (1) extracting highly active humic acid; the highly active humic acid extraction step in step (1) comprises:

[0044] A. After the weathered coal or lignite raw material is crushed, humic acid is extracted using 5% to 15% sodium hydroxide at 60°C to 90°C, and after filtering, the pH is adjusted to 1.0 to 3.0 to precipitate humic acid, which is then dried and crushed;

[0045] B. The extracted humic acid is reacted with ethylenediamine or sodium bisulfite at 40°C to 70°C for 1h to 5h to form modified humic acid, which is then mixed with trace elements of iron, zinc and copper, the pH is adjusted to 4.0 to 7.0, and stirred for 1h to 3h to obtain highly active humic acid.

[0046] (2) Modification of highly active humic acid and chelation of trace elements;

[0047] (3) After mixing the modified high-activity humic acid with nitrogen, phosphorus and potassium using a high-speed mixer, the particles are prepared using a spray drying technology; in step (3), the inlet temperature of the spray drying is 120° C. to 160° C., and the outlet temperature is 70° C. to 90° C.

[0048] (4) Fluidized bed coating technology is used to control the thickness of the coating layer of the core particles, wherein the inner layer is a blend of polylactic acid and polycaprolactone, the middle layer is a composite material of nano-silicon dioxide and nano-alumina, and the outer layer is a hydrogel prepared from a copolymer of chitosan and polyacrylic acid;

[0049] (5) Dry the coated particles by vacuum drying technology, and then pack them into bags for storage. The vacuum drying conditions in step (5) are: temperature of 40°C to 60°C, vacuum degree of 0.05MPa to 0.1MPa, and drying time of 2h to 6h, so as to ensure that the moisture content in the particles is reduced to less than 1%.

[0050] Specifically, the compound fertilizer includes the following components by mass percentage: 5% to 40% of highly active humic acid, 10% to 35% of nitrogen, 5% to 20% of phosphorus, 5% to 20% of potassium, and 0.1% to 5% of chelated trace elements, including metal ions such as iron, zinc, and copper that can significantly improve the absorption of trace elements by crops. In addition, the coating structure of the compound fertilizer consists of an inner layer, a middle layer, and an outer layer to achieve slow-release control of nutrients. The mass percentage of the inner layer coating material is 2% to 20%, which is a blend of polylactic acid (PLA) and polycaprolactone (PCL) in a ratio of 50:50 to 90:10, and 5% to 15% by mass of nano-silicon dioxide particles of the total inner layer coating material are added to the blend. The mass percentage of the middle coating material is 0.5% to 10%, and it is composed of a composite coating of nano-silicon dioxide and nano-alumina prepared by a sol-gel method, and its thickness ranges from 5μm to 30μm. The mass percentage of the outer coating material is 0.5% to 5%, and it is composed of a hydrogel prepared from a copolymer of chitosan (CS) and polyacrylic acid (PAA), wherein the mass ratio of chitosan to polyacrylic acid is 1:1 to 1:3, and the thickness of the outer coating material ranges from 5μm to 20μm. By rationally designing the thickness of the coating layer, the thickness of the inner coating material is controlled at 10μm to 50μm, the thickness of the middle coating material is controlled at 5μm to 30μm, and the thickness of the outer coating material is controlled at 5μm to 20μm, thereby ensuring that the compound fertilizer continuously releases nutrients in different growth cycles, meets the nutrient needs of crops at different stages, prolongs the fertilizer effect time, and reduces the frequency of fertilization, improves fertilizer utilization, and reduces potential pollution to the environment.

[0051] The preparation method of the composite fertilizer comprises the following steps:

[0052] (1) Extracting high-activity humic acid. In the high-activity humic acid extraction step, the weathered coal or lignite raw material is firstly pulverized to achieve a desired particle size, and then a 5% to 15% sodium hydroxide solution is used to extract the humic acid at a temperature of 60° C. to 90° C. The extraction step lasts for a certain period of time, usually 2 to 6 hours. The extracted solution is filtered to remove impurities, and then the pH is adjusted to 1.0 to 3.0 by gradually adding an acid (such as hydrochloric acid) to precipitate humic acid. The precipitate is dried at a drying temperature of 50° C. to 80° C., and then the dried humic acid is pulverized to a desired fineness, usually above 200 meshes;

[0053] (2) reacting the extracted humic acid with ethylenediamine or sodium bisulfite, controlling the reaction temperature between 40°C and 70°C, and reacting for 1h to 5h. This modification step introduces amino or sulfonic groups into the humic acid molecular chain, thereby enhancing its chelating ability. Subsequently, the modified humic acid is mixed with a solution of trace elements such as iron, zinc, and copper, and the pH is adjusted to 4.0 to 7.0. Alkaline substances (such as sodium hydroxide or ammonia water) are usually used for adjustment. After stirring and reacting for 1h to 3h, highly active humic acid is obtained. This step helps to enhance the stability of trace elements in compound fertilizers and plant absorption efficiency.

[0054] (3) In the process of preparing the core particles, the modified high-activity humic acid is firstly mixed with nitrogen, phosphorus and potassium compounds using a high-speed mixer to ensure uniform distribution of the components. The mixed slurry is then spray dried to prepare particles. During the spray drying process, the inlet temperature is controlled at 120°C to 160°C and the outlet temperature is controlled at 70°C to 90°C. This operation enables the obtained particles to have good fluidity and mechanical strength, and avoids the problem of agglomeration of the particles caused by humidity changes during storage and transportation. (4) The core particles are controlled by fluidized bed coating technology. The coating thickness of the particles is controlled by controlling the temperature and flow rate in the fluidized bed to ensure that the coating material is evenly covered on the surface of the particles. Then the middle coating is performed. The middle layer is a composite material of nano-silicon dioxide and nano-alumina. The function of this coating layer is to provide a long-term sustained release function through the high specific surface area of ​​the nanoparticles. Finally, the outer coating is performed. The outer layer is a hydrogel prepared from a copolymer of chitosan and polyacrylic acid. The hydrogel exhibits different expansion and contraction behaviors under different pH conditions, thereby controlling the release rate of nutrients.

[0055] (5) The coated particles are dried by vacuum drying technology. The drying conditions are as follows: the temperature is controlled between 40°C and 60°C, the vacuum degree is controlled between 0.05MPa and 0.1MPa, and the drying time is 2h to 6h to ensure that the moisture content in the particles is reduced to below 1%. Finally, the treated particles are bagged and stored for later use.

[0056] Summarize:

[0057] The highly active humic acid ecological compound fertilizer prepared by the above steps can effectively provide the required macro and micro nutrients during the growth of crops, and achieve a slow-release effect of nutrients through a multi-layer coating structure, reducing the frequency of fertilization and improving the utilization efficiency of fertilizers. At the same time, the compound fertilizer has good anti-caking properties and is suitable for different storage and transportation conditions. The method is easy to operate, cost-controlled, suitable for large-scale industrial production, and provides an efficient and environmentally friendly fertilizer solution for modern agriculture.

[0058] Embodiment 2:

[0059] Based on Example 1, the following implementation steps are given:

[0060] Preparation process:

[0061] (1) Extraction of highly active humic acid: 10 kg of weathered coal was crushed to a particle size of 100 mesh, 50 liters of 10% sodium hydroxide solution was added, stirred and reacted at 80°C for 4 hours. After the solution was filtered, the pH of the filtrate was adjusted to 2.0, and humic acid precipitate was precipitated. The precipitate was then dried to a water content of less than 5% and crushed to 200 mesh.

[0062] (2) Humic acid modification: The extracted humic acid was reacted with 1 kg of ethylenediamine solution at 60°C for 3 hours to introduce amino functional groups. Subsequently, 0.5 kg of a mixed solution of zinc sulfate, ferrous sulfate and copper sulfate was added, the pH was adjusted to 5.5, and the reaction was continued for 2 hours under stirring to obtain chelated high-activity humic acid.

[0063] (3) Preparation of core particles: The modified humic acid was mixed with 30 kg of urea (containing about 46% nitrogen), 10 kg of monoammonium phosphate (containing about 12% phosphorus), and 10 kg of potassium sulfate (containing about 50% potassium), and the core particles were prepared by spray drying. The inlet temperature of the spray dryer was set to 140°C and the outlet temperature was set to 80°C. The particle size range of the prepared particles was 2 to 3 mm, and more than 90% of the particles that met the national standard particle size requirements were between 1.00 mm and 4.75 mm.

[0064] (4) Multilayer coating: PLA and PCL were blended in a ratio of 70:30 in a fluidized bed to form an inner layer material, 10% by mass of nano-silicon dioxide particles were added, and the coating was carried out at 150°C. The inner layer coating thickness was controlled to be 20 μm. The middle layer used a nano-silicon dioxide and nano-alumina composite material prepared by the sol-gel method, and the coating thickness was controlled to be 10 μm. The outer layer used a hydrogel prepared from chitosan and polyacrylic acid copolymer, and the coating thickness was 15 μm.

[0065] (5) Vacuum drying and shaping: The coated particles were vacuum dried at 50°C for 4 hours with a vacuum degree of 0.08 MPa and a moisture content of less than 1%. They were then shaped at 120°C and 10 MPa to ensure uniform particle shape.

[0066] Summarize:

[0067] The compound fertilizer prepared in this embodiment has a uniform coating layer and excellent slow-release performance, and can gradually release nutrients within 3 to 6 months, which is suitable for the fertilization needs of long-cycle crops. The mechanical strength of the particles is good, avoiding possible dust problems during fertilization.

[0068] Embodiment 3:

[0069] Based on Example 1, the following implementation steps are given:

[0070] Preparation process:

[0071] (1) Extraction of highly active humic acid: 12 kg of lignite was crushed to 200 mesh, and then reacted with 15% sodium hydroxide solution at 90°C for 2 hours. After filtering, the pH was adjusted to 1.5 to precipitate humic acid. The precipitate was dried to a water content of less than 3%, and then crushed to 300 mesh.

[0072] (2) Humic acid modification: The extracted humic acid was reacted with 1.5 kg of sodium bisulfite at 70°C for 4 hours to introduce sulfonic functional groups, and then 1 kg of a mixed solution of zinc sulfate and copper sulfate was added, the pH was adjusted to 4.5, and the reaction was continued with stirring for 3 hours to obtain chelated high-activity humic acid.

[0073] (3) Preparation of core particles: The modified humic acid was mixed with 25 kg of ammonium sulfate (containing about 21% nitrogen), 10 kg of calcium hydrogen phosphate (containing about 18% phosphorus), and 10 kg of potassium chloride (containing about 50% potassium), and then spray dried using a spray dryer. During the drying process, the inlet temperature was set to 130°C and the outlet temperature was set to 75°C. The particle size range of the obtained particles was 1.5 to 2.5 mm, which met the particle size requirements of the national standard GB / T 15063-2020, that is, more than 90% of the particles must have a particle size between 1.00 mm and 4.75 mm.

[0074] (4) Multilayer coating: PLA and PCL were blended in a ratio of 60:40 as the inner layer material, 15% by mass of nano-silicon dioxide particles were added, and the coating was carried out at 140°C. The inner layer coating thickness was 30 μm. The middle layer was a composite coating of nano-silicon dioxide and nano-alumina with a thickness of 15 μm. The outer layer was a hydrogel of chitosan and polyacrylic acid with a thickness of 20 μm.

[0075] (5) Vacuum drying and shaping: The coated particles were vacuum dried at 60°C for 3 hours with a vacuum degree of 0.07 MPa until the moisture content dropped below 1%, and then shaped at 150°C and 15 MPa.

[0076] Summarize:

[0077] The compound fertilizer of this embodiment has a thicker coating layer, provides a longer nutrient release period, and is suitable for crop planting in a higher temperature and higher humidity environment. The granules have a higher compressive strength and are suitable for mechanical fertilization operations.

[0078] Embodiment 4:

[0079] Based on Example 1, the following implementation steps are given:

[0080] Preparation process:

[0081] (1) Extraction of highly active humic acid: 8 kg of weathered coal was crushed to 150 mesh, and humic acid was extracted using 8% sodium hydroxide solution at 70°C for 5 hours. After filtration, the pH of the filtrate was adjusted to 2.5, the precipitate was dried to a water content of less than 4%, and crushed to 200 mesh.

[0082] (2) Humic acid modification: The extracted humic acid was reacted with 0.8 kg of ethylenediamine at 50°C for 2 hours, and then 0.4 kg of a mixed solution of zinc sulfate and ferrous sulfate was added, the pH was adjusted to 6.5, and the reaction was stirred for 2 hours to obtain chelated high-activity humic acid.

[0083] (3) Preparation of core particles: The modified humic acid was mixed with 20 kg of ammonium sulfate (containing about 21% nitrogen), 5 kg of potassium nitrate (containing about 13% nitrate nitrogen and about 46% potassium), 10 kg of calcium hydrogen phosphate (containing about 18% phosphorus) and 5 kg of potassium chloride (containing about 50% potassium), and then spray dried using a spray dryer. During the drying process, the inlet temperature was set to 130°C and the outlet temperature was 75°C. The particle size range of the obtained particles was 1.5 to 2.5 mm, which met the particle size requirements of the national standard GB / T 15063-2020, that is, more than 90% of the particles must have a particle size between 1.00 mm and 4.75 mm.

[0084] (4) Multilayer coating: The inner coating material is a mixture of PLA and PCL in a ratio of 80:20, with 5% by mass of nano-silicon dioxide particles added, and the coating is carried out at 130°C. The inner layer thickness is controlled at 15 μm. The middle layer is a composite material of nano-silicon dioxide and nano-alumina, and the coating thickness is controlled at 20 μm. The outer layer uses a hydrogel of chitosan and polyacrylic acid, with a thickness of 10 μm.

[0085] (5) Vacuum drying and shaping: The coated particles were vacuum dried at 40°C for 6 hours with a vacuum degree of 0.1 MPa to ensure that the moisture content was below 1%, and then shaped at 100°C and 5 MPa.

[0086] Summarize:

[0087] The compound fertilizer prepared in this embodiment is suitable for use in low temperature environments, has a thin coating layer, can quickly release nutrients, and is suitable for short-term crops or fast-growing economic crops. The particle structure is compact and easy to store and transport.

[0088] Summary:

[0089] In the three embodiments, the formula and coating structure of the compound fertilizer are adjusted according to different environmental conditions and crop requirements. The compound fertilizer of embodiment 1 is suitable for long-cycle crops and provides uniform and continuous nutrient release; embodiment 2 increases the coating layer thickness, is suitable for high temperature and high humidity environments, and prolongs the nutrient release cycle; embodiment 3 is more suitable for short-cycle crops or economic crops, can quickly release nutrients and adapt to low temperature environments.

[0090] Test experiment and comparative experiment:

[0091] Test experiment:

[0092] The nutrient release cycle involved in this experiment was determined through laboratory and field tests. In the laboratory, the nutrient release of the fertilizer was monitored using water solubility tests and soil culture tests. In the water solubility test, the fertilizer was soaked in water at a constant temperature, and samples were taken every 7 days to measure the nitrogen, phosphorus, and potassium nutrient content in the water until the nutrient release was completed;

[0093] In soil culture experiments, fertilizers are applied to soil containers that simulate agricultural conditions, and changes in nutrient content in the soil are monitored regularly.

[0094] Combining these data, it was deduced that the nutrient release period of slow-release fertilizers is 6 months, 9 months, or 3 months, depending on the differences in fertilizer formulation and coating materials.

[0095] The compound fertilizers of the three embodiments were applied to corn planting under different environmental conditions to monitor the nutrient release rate, crop growth status and fertilizer efficiency. The tests were conducted under wet, dry, high temperature and low temperature environments. The data recorded included: plant height, chlorophyll content, root system development, single plant yield, and soil nutrient residue.

[0096] project Example 2 Example 3 Example 4 Nutrient release cycle 6 months 9 months 3 months Plant height (cm) 180 175 160 Chlorophyll content (SPAD) 52 50 48 Root length (cm) 45 42 38 Yield per plant (g) 120 115 105 Soil nitrogen residue (ppm) 10 8 15

[0097] Comparative experiment 1:

[0098] The experiment was carried out under the same conditions as ordinary commercial compound fertilizers to compare the fertilizer efficiency and fertilization frequency.

[0099] Comparative experiment 2:

[0100] The nutrient release stability of the compound fertilizer under different temperatures and humidity was analyzed by comparing it with commercially available slow-release compound fertilizers.

[0101] Comparative experiment 3:

[0102] In the field test, the compound fertilizers of Examples 2, 3, and 4 were compared with conventional fertilization schemes, including soil health indicators (such as pH value, microbial activity) and crop yields.

[0103] Experimental data table and specific parameters:

[0104]

[0105] Summarize:

[0106] Through the above experiments and comparisons, it is clear that highly active humic acid ecological compound fertilizer has significant advantages in nutrient release stability, fertilization efficiency, and soil health maintenance, especially in reducing fertilization frequency and increasing crop yield. The three embodiments provide effective solutions for different crop types and growth environments, demonstrating the potential for wide application of highly active humic acid ecological compound fertilizer in modern agriculture.

[0107] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A highly active humic acid ecological compound fertilizer, characterized in that: The following components are included in mass percentage: 5% to 40% highly active humic acid; 10% to 35% nitrogen; 5% to 20% phosphorus; 5% to 20% potassium; 0.1% to 5% chelated trace elements; 2% to 20% inner coating material; 0.5% to 10% of middle layer coating material; 0.5% to 5% outer coating material.

2. A highly active humic acid ecological compound fertilizer according to claim 1, characterized in that: The inner layer coating material is a mixture of polylactic acid and polycaprolactone in a ratio of 50:50 to 90:10, and 5% to 15% by mass of nano silicon dioxide particles are added into the mixture.

3. A highly active humic acid ecological compound fertilizer according to claim 1, characterized in that: The middle layer coating material is a composite coating of nano silicon dioxide and nano aluminum oxide prepared by a sol-gel method, and the thickness thereof is 5 μm to 30 μm.

4. A highly active humic acid ecological compound fertilizer according to claim 1, characterized in that: The outer coating material is a hydrogel prepared from a copolymer of chitosan and polyacrylic acid, and the mass ratio of chitosan to polyacrylic acid is 1:1 to 1:

3.

5. The highly active humic acid ecological compound fertilizer according to claim 1, characterized in that: The thickness of the inner layer coating material is 10 μm to 50 μm, the thickness of the middle layer coating material is 5 μm to 30 μm, and the thickness of the outer layer coating material is 5 μm to 20 μm.

6. The highly active humic acid ecological compound fertilizer according to claim 1, characterized in that: The chelated trace elements include one or more of iron, zinc and copper.

7. A method for preparing a highly active humic acid ecological compound fertilizer, comprising preparing a highly active humic acid ecological compound fertilizer according to any one of claims 1 to 6, characterized in that: The following steps are involved: (1) Extraction of highly active humic acid; (2) Modification of highly active humic acid and chelation of trace elements; (3) using a high-speed mixer to mix the modified high-activity humic acid with nitrogen, phosphorus and potassium, and then using spray drying technology to prepare particles; (4) Fluidized bed coating technology is used to control the thickness of the coating layer of the core particles, wherein the inner layer is a blend of polylactic acid and polycaprolactone, the middle layer is a composite material of nano-silicon dioxide and nano-alumina, and the outer layer is a hydrogel prepared from a copolymer of chitosan and polyacrylic acid; (5) The coated particles are dried using vacuum drying technology and then bagged for storage.

8. The method for preparing a highly active humic acid ecological compound fertilizer according to claim 7, characterized in that: The high-activity humic acid extraction step in step (1) comprises: A. After the weathered coal or lignite raw material is crushed, humic acid is extracted using 5% to 15% sodium hydroxide at 60°C to 90°C, and after filtering, the pH is adjusted to 1.0 to 3.0 to precipitate humic acid, which is then dried and crushed; B. The extracted humic acid is reacted with ethylenediamine or sodium bisulfite at 40°C to 70°C for 1h to 5h to form modified humic acid, which is then mixed with trace elements of iron, zinc and copper, the pH is adjusted to 4.0 to 7.0, and stirred for 1h to 3h to obtain highly active humic acid.

9. The method for preparing a highly active humic acid ecological compound fertilizer according to claim 7, characterized in that: The vacuum drying conditions in step (5) are: temperature of 40° C. to 60° C., vacuum degree of 0.05 MPa to 0.1 MPa, and drying time of 2 h to 6 h, to ensure that the moisture content in the particles is reduced to below 1%.

10. The method for preparing a highly active humic acid ecological compound fertilizer according to claim 7, characterized in that: In the step (3), the inlet temperature of the spray drying is 120°C to 160°C, and the outlet temperature is 70°C to 90°C.